Answers

2014-04-24T16:37:36+05:30
Look at the diagram
u can see by cosine law
CX²=BC²+BX^2-2(BC)(BX)cos(60)
CX²=BC²+AB^2-(BC)(AB)...(1)
similarly
BY²=BC²+CY²-2(BC)(CY)cos(60)
BY²=BC²+AC²-(BC)(AC)
as AB=AC
BY²=BC²+AB^2-(BC)(AB)..(2)
(1)=(2)
therefore
BY=CY


1 5 1
2014-04-25T19:48:01+05:30
In eqilateral triangle all the sides are equal . measure angle ABX=60 thus ab=bx=ax=60
thus it is an eqilateral triangle and as per given data abx=acy thus cx =by
0
IF ABC is not an equilateral triangle?
i think then it forms right angled triangle where we apply the pythagoras theorum